Influence of perception of tax fairness, social media, religiosity and customs law on import duty non compliance behaviour in Malaysia - Yusoff, Yusri Hazrol (2019)
The issue of tax noncompliance has been critically discussed by the Malaysian Government and academic researchers due to the fact that the tax noncompliance directly affects the source of national income. Indirectly, the noncompliance affects the social and economic development of a country. In Malaysia, the Royal Malaysian Customs Department (RMCD) is responsible for administering and enforcing the law of indirect taxes including import duty. Despite the legal implementation over 50 years, tax noncompliance remains sticky and increases at an alarming rate. Various strategies and actions have been invested in mitigating the worsening issue. Existing actions taken are mostly related to the economic factors such as raising penalties, increasing the number of operations and inspections, adding the number of enforcement officers and claiming tax debts through court action. In order to overcome this problem, this study points out the equal importance of the agency and policy makers to view and resolve this issue through the non-economic perspectives for a number of reasons. First, the actions of a non-economic factors are more closely related to the action in which behaviour of taxpayers or importer can be controlled before the noncompliance takes place. Second, preventive and controlling measures of noncompliance can be enhanced as it saves time, energy and cost for solving the issue when it occurs. In order to understand the Malaysian taxpayer’s noncompliance behaviour, the study intends to adapt the Theory of Planned Behaviour (TPB) to describe behaviour and actions taken by the noncompliant taxpayers. In addition, this study proposes import duty as it involves with the highest number of Bill of Demand (BOD) issued by the RMCD in comparison with other indirect taxes. As a matter of fact, import duty accounts for the highest contribution in indirect taxes. This situation signifies a severe matter to the agency and policy makers as it potentially leads to serious leakage in the national revenue. Therefore, studying the taxpayers’ behaviour in case of import duty is strongly relevant based on the belief that if the noncompliance issue can be gradually solved, it will offer a positive impact on the economic, social and national development. Using a quantitative research approach, survey questionnaires were distributed to 636 company that the listed under BOD. Partial Least Squares (PLS) software was applied to examine the direct and mediating effect hypotheses. The results revealed that non-economic factors have a relationship with Import Duty noncompliance behavior. Moreover, Behavioural Intention (Intention Not to Comply) is strongly support as mediator between non-economic factor and noncompliance behavior in the indirect tax. Except, Perception of Tax Fairness has direct relationship with noncompliance behavior. The results will be useful to the Indirect tax systems in developing proper strategy to combat noncompliance issue especially in Malaysia. Policy makers (Royal Malaysia Customs Department) could also benefit from this study by providing advisory services and assistance programs that could help the taxpayers in improving their compliance. The study has successfully filled the gap in literature by empirically establishing the relationship between non-economic factors (Perception of Tax Fairness, Social Media, Customs Law and Religiosity) and Import Duty Noncompliance Behavior. The study has also contributed to the existing body of knowledge in indirect tax systems by integrating the non-economic factor with adopted Theory Planned Behavior context into current research framework.